Identificação de punicalagina das folhas de Lafoensia pacari (Lythraceae) e avaliação das atividades biológicas - Chaibub, Beatriz Abdallah (2013)
Lafoensia pacari (Lythraceae) is a native plant of the Brazilian cerrado know as pacari. Studies showed anti-inflammatory, anti-oxidant e antinociceptive activities. This work aimed to isolate and identify chemical compounds and biological activities as anti-inflammatory, antiulcer, antissecretory, angiogenic and healing of the extract of the leaves and of an isolated from L. pacari. Initially we prepared and characterized the plant drug and was obtained the crude extract of pacari (EBP) in acetone 50% v/v. The extract was characterized and lyophilized for user in testing of biological activities. Then we did the fractionation of EBP with ethyl acetate and methanol. Chromatography of the fraction soluble in methanol was performed on a column of Diaion ® HP-20 and was monitored the chromatographic profile by thin layer chromatography. After collecting the fractions, we evaluated the chromatographic profile by High Performance Liquid Chromatography (HPLC) and the isolated compound was analyzed by nuclear magnetic resonance (NMR), obtaining one-dimensional and two-dimensional spectra. It was validated a HPLC method for quantification of punicalagin according to parameters of the National Agency for Sanitary Vigilance. The biological activities evaluated for EBP lyophilized and punicalagin followed the experimental models: anti-inflammatory activity in the croton oil-induced ear edema assay (EBP 5 mg / ear), antiulcer activity of gastric lesions induced by indomethacin (EBP 150 mg / kg and punicalagin 120 mg / kg), evaluation of antisecretory activity gastric acid in pylorus-ligation model (EBP 75, 150, 300 mg / kg and punicalagin 120 mg / kg), angiogenic activity in the chorioallantoic membrane model (CAM) (EBP 10 %) and the wound healing activity of cutaneous wound model in rats (EBP 10%). During the characterization of plant drug and EBP, we could confirm the presence of tannins. The yield of lyophilized EBP was 37.6%. In the HPLC analysis verified the presence of two peaks in the majority EBP, indicated that they are the same compound after the analysis of its UV absorption spectrum. After column chromatography and monitoring of the chromatographic profile, the fractions obtained were collected in 12 fractions (PAC) and observed that the PAC 2-7 showed the same chromatographic profile, and the total yield of 67.23%. The PAC 6 was analyzed for its one and two-dimensional NMR experiments, which allowed the structural elucidation of punicalagin, a hydrolysable tannin of the ellagitannins class. The validated method for punicalagin proved to be selective, linear, precise, accurate and robust. The content of punicalagin quantified in EBP was 65%. The EBP (5 mg / ear) showed anti-inflammatory activity by reducing edema of ear (41.44%, p < 0.001). The EBP at a dose of 150 mg / kg and punicalagin at a dose of 120 mg / kg reduced the rate of gastric damage following indomethacin administration of 29,82 (p ≤ 0.05) and 52.03% (p ≤ 0.001), respectively. In the evaluation of the parameters of acid secretion, the EBP and punicalagin were able to significantly reduce the volume (9.64%, p ≤ 0.05; 11.24 %, p ≤ 0.05, 15.66%, p ≤ 0.001) for EBP in the respective doses of 75, 150, 300 mg / kg and in punicalagin 9.69%, p ≤ 0.05 (to 120 mg / kg) a free acidity (76.89%, p ≤ 0.01, 58.97%, p ≤ 0.01, 49.66%, p ≤ 0.001) for EBP in the repective doses of 75, 150, 300 mg/kg and punicalagina at 22.47%, p ≤ 0.05 (for the 120 mg / kg) and total acidity (65.30%, p ≤ 0.001, 71.46%, p ≤ 0.001; 69.40, p ≤ 0.001) to EBP in the respective doses of 75, 150, 300 mg/kg and in punicalagin 41.98%, p ≤ 0.01 (to 120 mg / kg) acid secretion in mice 4 hours after pyloric ligation. The EBP 10% showed angiogenic property in the MCA model, decreased time to healing of wounds in rats and significantly increased two parameters involved in wound healing, the number of vessels and collagen production. This is the first study of the leaves of L. pacari demonstrating the presence of punicalagin and anti-inflammatory, antiulcer, antissecretory, angiogenesis activities and decreased healing time of EPB and punicalagin.